Upper gastrointestinal EMR service: long-term feasibility, safety, efficacy and cost effectiveness from a large UK centre. (13th March 2011) - Basford, P J; Mead, R J; Duku, M D; Longcroft-Wheaton, G R; Somers, S; Toh, S; Mercer, S; Poller, D; Cowlishaw, D; Bhandari, P
Abstract : Introduction: Endoscopic resection (ER) is an accepted treatment of early upper gastrointestinal neoplasia in Europe, but surgery remains the gold standard in the UK due to lack of data. We started an upper gastrointestinal ER service in 2005 and are reporting our 6 year outcome data. We serve six different regional cancer centres. Methods: We analysed our database of all upper gastrointestinal (UGI) endoscopic resection procedures performed at our centre for the period 2005–2010. All procedures were carried out by a single skilled endoscopist. Demographic data, histology, procedure success, long-term outcome and complications were assessed. Results: We have performed 160 UGI ER procedures (108 oesophageal (O), 29 gastric (G), 33 duodenal/ampullary (D)) in 127 patients (O=75, G=25, D=27). Mean age was 65.9 years (range 25–94). A mean of 1.32 UGI ER procedures were performed per patient (range 1–5). All neoplastic cases were diagnosed as high grade dysplasia or intramucosal cancer prior to EMR. Overall complication rate was 5.0%. Specific complications were four procedural bleeds and two delayed bleeds (all controlled endoscopically) one full thickness perforation clipped endoscopically and one episode of pancreatitis. There were no cases of procedure related mortality. 25 patients (19.7%) were upstaged, having been found to have sm1 invasion or deeper on histological examination of the initial ER specimen. This group were considered for radical treatment if fit, or conservative management if unfit or through patient choice. 16 patients (O=11, G=4, D=1) proceeded to radical surgery, of which 2 patients died of postoperative complications and 2 patients died of local recurrence; the other 12 remain well. 2 patients received chemo/radiotherapy; 1 died of advanced oesophageal cancer, the other remains well. Of the remaining 102 patients complete local remission was achieved in 79.4% of cases following a single ER procedure, and in 97.1% overall. After a mean 2.57 years follow-up; 4% of all patients are known to have recurrence or metachronous disease and are awaiting further ER. Development of our service has potentially led to a cost saving of £91 270 per year, plus 170 bed days saved per year through reduced requirement for radical surgery. Conclusion: Our data demonstrates the long-term feasibility, efficacy and safety of an innovative ER service. It provides valuable information about the number and type of patients requiring this service helping inform future planning and commissioning. Our data demonstrates significant cost savings for the NHS.